Implementation of Muslim Family Maintenance Responsibilities After the Death of the Husband (Case Study of Al Binaa Islamic Boarding School) - Azzahra, Fatimah; Muhtadin, Sabilul (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2025)
The obligation of family maintenance (nafkah) is a fundamental principle in Islamic family law, primarily assigned to the husband as the head of the household. However, when the husband passes away, the fulfillment of family maintenance often becomes a complex socio-economic issue. In this context, the role of socio-religious institutions is crucial in safeguarding the welfare of families left behind. This study aims to analyze the implementation of the responsibility for sustaining Muslim families after the husband’s death within the Al Binaa Islamic Boarding School environment, as well as to examine the role of the boarding school in maintaining family welfare through economic, social, and spiritual support. The research employs a descriptive qualitative method with a case-study approach through surveys. Data were collected using both closed and open questionnaires distributed online to six purposively selected respondents, namely wives or family members who directly experienced the condition following the husband’s death. The data were analyzed descriptively to understand patterns of sustenance support and practices of social solidarity within the boarding school community. The findings reveal that Al Binaa Islamic Boarding School plays an active role in supporting bereaved families through various forms of assistance, such as covering children’s educational expenses, providing housing, financial aid, and spiritual guidance. These findings affirm that the boarding school functions as a religious institution that integrates the values of Islamic family law with social practices based on the principle of ta’awun (mutual assistance) in preserving family welfare. This study offers a reconceptualization of sustenance obligations in contemporary Islamic law, shifting the paradigm from a contractual-individual framework to a covenantal-communal one. Practically, this model provides a framework for boarding school-based social protection policies that can be integrated with the national social security system.